Application Of Boyer Moore Algorithm for Text Searching - Fince Tinus Waruwu (The IJICS (International Journal of Informatics and Computer Science), 2017)
Technology at the moment is very rapid development in business, and education. Many developers or application makers are competing in improving science about the science of technology so as not to miss. Technology is an integral part of human life. Computer application is one part that is not separated from the computer. An application is a software that actually works to simplify the job. Thus, at this time already many computer applications are created. In the course, the application software always experienced improvements made by the manufacturer. These improvements lead to improved facilities to make it easier for users to work. In the world of education or the world of work a lot of work done by using computers such as typing by using text editor applications such as Microsoft Word in the manufacture of scientific work or other work, often mistakes in terms of writing words, often mistakes occur not because of intentional but because of community habits In abbreviating words when writing. It is necessary an application that can facilitate the examination of a writing in order to find the wrong word or abbreviated and automatically the application will fix it (text improvement). To make it easier to find the wrong word in the application, it needs string matching technique using Boyer Moore algorithm. The application is built with Microsoft Visual Studio 2008 and MySQL as the.